The Effects of Perceived Justice and Emotions on Service Recovery Satisfaction on Indonesian Ecommerce Customers - Fatimah Azzahro; Putu Wuri Handayani; Sandya Sekar Murti; Satrio Baskoro Yudhoatmojo (Faculty of Computer Science Universitas Indonesia, 2020)
This study aims to analyze the effects of justice theory and emotions on service recovery satisfaction of Indonesian e-commerce customers. The factors used in this study are distributive justice, procedural justice, interactional justice, as cognitive aspect. Positive emotions and negative emotions are the factors used as affective aspect. This study used quantitative approach in the form of online survey. The total amount of data used in this study are 601 data. The respondents are Indonesian B2C or C2C e-commerce customer who filed a complaint directly to the B2C or C2C e-commerce at least once and receives a response at least once. Covariance-based structural equation modelling is used to analyze the data. The analysis results show that distributive justice, procedural justice, interactional justice, and positive emotions affect service recovery satisfaction. The results of this study can help Indonesian B2C & C2C e-commerce to understand service recovery from the perspective of customers, so satisfactory service recovery can be implemented.